Peningkatan Kreativitas Dan Literasi Digital Peserta Didik Melalui Metode Resitasi Dalam Pembuatan Film Pendek Sejarah - Siti Khoimah (Jurnal Didaktika Pendidikan Dasar, 2020)
The Industrial Revolution 4.0 requires the world of education to participate in developing a knowledgeable society with the characteristics of having 21st century skills that are creative and have digital literacy capabilities to be able to compete globally. Social studies learning is identical with rote learning and difficult for students to understand, so teachers are expected to continue to innovate so that learning becomes more active and dynamic. The purpose of this study was to determine whether the recitation method in making historical short films can increase students' creativity and digital literacy. The subjects in this study were students of class VIII-A at Al Abidin Islamic Middle School Surakarta in the Academic Year 2017/2018 Semester 2 as many as 35 people. The instrument used to assess creativity is to use the rubric of creativity assessment, observation, and self-assessment of students. Digital literacy assessment uses the digital literacy assessment rubric and student self-assessment. The results showed that the recitation method in making historical short films was able to increase students' creativity and digital literacy. In the first cycle of research, the creativity of students obtained an average value of 72.5. This figure shows that students are already in the creative category. Digital literacy of students obtained an average value of 62.5, also included in the category quite well. In the second cycle research the average value of students' creativity increased to 81.3 in the very creative category, and the digital literacy of students increased to 75.0, with a good category. Observation results show that the recitation method in making historical short films can improve students' creativity and digital literacy.